Efficacy and safety of Jinghua Weikang capsule combined with amoxicillin-furazolidone triple/quadruple therapies in the rescue treatment of Helicobacter pylori infection - Yang, Yao; Deng, Xin; Xiao, Hui-Xia; Ye, Su-Man; Wang, Zi-Cheng; Jiang, Feng; Han, Hai-Xiao; Wang, Zai-Jian; Ma, Ji-Zheng; Lan, Yu; Ye, Hui; Zhang, Xue-Zhi (Frontiers in Medicine, 2025)
AimTo evaluate the efficacy and safety of Jinghua Weikang Capsule (JWC) combined with amoxicillin-furazolidone triple/quadruple therapies in the rescue treatment of drug-resistant H. pylori infection.MethodsPatients who failed H. pylori eradication therapy at least once were enrolled and randomly assigned into four groups (1:1:1:1), as follows: The control group received 20 mg rabeprazole, 1,000 mg amoxicillin, 220 mg bismuth potassium citrate, and 100 mg furazolidone twice daily (b.i.d.) for 14 days; Group A received 240 mg JWC b.i.d. combined with 20 mg rabeprazole, 1,000 mg amoxicillin, and 100 mg furazolidone b.i.d. for 14 days; Group B received the same regimen as Group A for 14 days, followed by an additional 14 days of 240 mg JWC b.i.d.; and Group C received 240 mg JWC b.i.d. combined with 20 mg rabeprazole, 1,000 mg amoxicillin, 220 mg bismuth potassium citrate, and 100 mg furazolidone b.i.d. for 10 days. The primary outcome was H. pylori eradication at 4 weeks after treatment.ResultsFour hundred eighty-eight patients were included in this study. The intention-to-treat (ITT) eradication rates in the four groups were 85.2, 73.8, 78.7 and 75.4% (p = 0.136), while the modified intention-to-treat (MITT) eradication rates were 92.0, 84.9, 88.9 and 86.8% (p = 0.398), respectively. And the per-protocol (PP) eradication rates were 92.5, 85.4, 87.9 and 86.7% (p = 0.405), respectively. The eradication rates were comparable among the four groups. No statistically significant differences in eradication rates were observed between each of the three treatment groups and the control group (all p > 0.05). The eradication rate of H. pylori in group B demonstrated non-inferiority compared with the control group (p = 0.0415; 90% CI, −0.0965 to 0.0336). The four groups exhibited similar frequencies of overall adverse events (9.84, 5.74, 6.56%, 2.46%, p = 0.112).ConclusionThe eradication rate of the JWC-containing regimen demonstrated no statistically significant difference compared with bismuth-containing quadruple therapy in the rescue treatment of H. pylori infection. The prolonged JWC treatment regimen exhibited non-inferiority in eradication rates. JWC-containing therapies can effectively reduce the incidence of adverse reactions and significantly alleviate certain clinical symptoms.Clinical trialhttps://clinicaltrials.gov/, identifier ChiCTR1800019326.